665 A Nationwide Study Characterizing the Risk and Outcome Profiles of Multilevel Fusion Procedures in Neuromuscular Scoliosis Patients With Neurofibromatosis Type 1. (April 2023) - Price, Gabrielle; Martini, Michael Louis; Caridi, John M.; Lau, Darryl; Oermann, Eric Karl; Neifert, Sean N.
Abstract : INTRODUCTION: Spine abnormalities are a common manifestation of Neurofibromatosis Type 1 (NF1); however, the outcomes of surgical treatment for NF1-associated spinal deformity are not well explored. METHODS: The National Inpatient Sample was queried for NF1 and non-NF1 patient populations with neuromuscular scoliosis who underwent multilevel fusion surgery involving eight or more vertebral levels between 2004 and 2017. Multivariate regression modeling was used to explore the relationship between perioperative variables and pertinent outcomes. RESULTS: Of the 55, 485 patients with scoliosis, 533 patients (0.96%) had NF1. Patients with NF1 were more likely to have comorbid solid tumors (p < 0.0001), clinical depression (p < 0.0001), peripheral vascular disease (p < 0.0001), and hypertension (p<0.001). Following surgery, NF1 patients had a higher incidence of hydrocephalus (0.6% vs. 1.9% p=0.002), seizures (4.9% vs. 5.7% p = 0.006), and accidental vessel laceration (0.3% vs. 1.9% p = 0.011). Although there were no differences in overall complication rates or in-hospital mortality, multivariate regression revealed NF1 patients had an increased probability of pulmonary (OR 0.5, 95% CI 0.3-0.8, p = 0.004) and neurological (OR 1.8, 95%CI 1.0-3.3, p = 0.053) complications. There were no significant differences in utilization, including non-home discharge or extended hospitalization; however, patients with NF1 had higher total hospital charges (OR -$18739, SE 3384, p < 0.0001). CONCLUSIONS: These findings indicate that NF1 is associated with certain complications following multilevel fusion surgery but does not appear to be associated with differences in quality or cost outcomes. These results provide some guidance to surgeons and other healthcare professionals in their perioperative decision making by raising awareness about risk factors for NF1 patients undergoing multilevel fusion surgery. We intend for this study to set the national baseline for complications after multilevel fusion in the NF1 population.